Influence of coil shapes on temperature distribution in induction heating process. (2023) - Patil, Mayur; Kumar Choubey, Rahul; Kumar Jain, Prashant
Abstract: Induction heating technology has been widely applied in industrial applications like preheating, brazing, and melting furnaces. In induction heating, eddy currents are induced internally in the workpiece, restriction in these eddy currents due to resistance of material dissipates energy and generates heat into the workpiece. In these processes, obtaining desired temperature profile for homogenized processing of the workpiece can be a very challenging task, here coil geometry can play a significant role in the resulting temperature distribution obtained on the workpiece. This paper provides an improved knowledge of the induction heating process through numerical simulation as well as helps in understanding the relationship between magnetic flux density distribution and resulting heating patterns. Four different shapes of the helical coil including classical, conical, square, and oval are analyzed. Their resulting magnetic fields and temperature control profiles are computed using the finite element method. Results obtained show that different shapes of coil produce different heat patterns. These results can be further applied to predict the heating zones and assist in designing induction heating coils for the induction heating applications like thixoforming, in order to achieve desired temperature profiles.